Kontroversi Ajaran Doktrin Tritunggal di Masa Kini: Urgensi Teologi Pembebasan Atau Sensasi - Georges Nicolas Djone (Formosa Journal of Science and Technology, 2022)
The purpose of writing this article is to examine the controversy over the doctrine of the Trinity Doctrine today, as well as to analyze the relevance of the urgency of liberation theology to this teaching today, using a descriptive qualitative method approach through literature analysis and data collection techniques through Bible sources, various books and journals, as well as  various documents related to the object of research. As a result, there is a massive effort to evoke Sabelianism in terms known as “Oneness Pentacostalism” today, especially in Indonesia. In conclusion, the Call for Liberation Theology and the controversy surrounding the Trinity Doctrine is not a sensation in a massive effort to evoke Sabelianism in terms known as "Oneness Pentacostalism" today, especially in Indonesia, so that the relevance of the urgency of the call for a liberation theology to the term  and the Trinity teaching is not clear and has the same basis as in the past, even today it is still not strong because precisely the Trinity is not only a characteristic of Christian belief, but also the only way of understanding the Living and perfect God YHWH insofar as He reveals Himself to  His people and also in this world.